PENGARUH KUALITAS PELAYANAN, KEMAMPUAN MANAJERIAL PENGURUS, MOTIVASI ANGGOTA DAN CITRA KOPERASI TERHADAP KEPUASAN ANGGOTA KOPERASI WAHANA ARTHA NUGRAHA - Sinaga, Astri Ocktora; Kusumantoro, Kusumantoro (Fakultas Ekonomi, Universitas Negeri Semarang, 2015)
The cooperation can be superior to another business entity by providing good quality services and qualify in managing the cooperation and give the encouragement toward members as well as deliver good impression and gaining the conviction that cooperation memberâs have in meeting the level of memberâs satisfaction. There are several questioning of this research such as (1) Is there any influence quality ofÂ services, the capability of managerial boards, the motivation and image of cooperationâs members in satisfying them either partially or simultaneously? (2) How much the influence quality of services, the capability of managerial boards, the motivation and image of cooperationâs members in satisfying them either partially or simultaneously? Then, here are the objectives that can fully support this research in order to research questions above such as (1) To determine the effects quality of services, the capability of managerial boards, the motivation and image of cooperationâs members in satisfying them either partially or simultaneously? And (2) To determine the influence quality of services, the capability of managerial boards, the motivation and image of cooperationâs members in satisfying them either partially or simultaneously? The population of this research was the whole number of The Wahana Artha Nugraha Cooperationâs Members Semarang with the total was thirty eight members. The number of sample is all entire amount of population. The research methodology in collecting data of this research used questionnaires and documentation. Also the analysis methodology of this research used descriptive and inferential statistical analysis.The result of this research showed that there was significant quality of services, the capability of managerial boards, the motivation and image of cooperationâs members in satisfying them directly with the amount 61.1%. Meanwhile, the partially showed that the amount quality of services was 18.92%, the capability of managerial boards was 26.52%, the influencing motivation members was 15.52%, and the cooperation image showed 23.3% in order to meet the satisfaction of cooperation members.Therefore, based on the satisfaction of cooperation members result of this researchcan be concluded that there was still significant quality of services, the capability of managerial boards, the motivation and image of cooperationâs members in satisfying them either partially or simultaneously.